2017
DOI: 10.17221/54/2016-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of "Wooden Breast" appearance on poultry meat quality, histological traits, and lesions characterization

Abstract: Dalle Zotte A., Tasoniero G., Puolanne E., Remignon H., Cecchinato M., Catelli E., Cullere M. (2017): Effect of "Wooden Breast" appearance on poultry meat quality, histological traits, and lesions characterization. Czech J. Anim. Sci., 62, 51-57.The purposes of the study were to investigate the effects of Wooden Breast (WB) myodegeneration on poultry meat quality and to give a contribution in typing lesions morphology. At a poultry meat cutting facility, 474 carcasses of a high-breast-yield hybrid chickens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
72
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 29 publications
16
72
2
2
Order By: Relevance
“…for WBs. However, the color characterization of WB chicken is still divergent, mainly due to the points of bleeding that change the meat surface …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…for WBs. However, the color characterization of WB chicken is still divergent, mainly due to the points of bleeding that change the meat surface …”
Section: Resultssupporting
confidence: 93%
“…However, the color characterization of WB chicken is still divergent, mainly due to the points of bleeding that change the meat surface. 2,15,16,33 TPA and tenderness during frozen storage of WB chicken sausage Figure 3 shows the effect of WB and storage time on the SF and texture profile analysis (TPA) values of the chicken sausages.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%
“…There is a consensus on the impaired functionality of WB and WS and that such adverse condition is more intense at higher severity degrees of the myopathy (Tijare et al., ). Among the three muscle lesion types, WB displays particularly poor functionality which is manifested in low yields, impaired marinade uptake and reduced ability to hold water under both raw (increased drip loss) and heat treatment conditions (increased cooking loss) (Dalgaard et al., ; Dalle‐Zotte et al., ; Kuttappan et al., , Mudalal et al., ; Soglia et al., ). Bowker, Maxwell, Zhuang, and Adhikari () recently evaluated the performance of severe WB fillets during marination (0.75% NaCl/0.45 sodium phosphate) and oven‐cooking (78 °C) and found that the marinade uptake and subsequent retention was lower in WB samples than in the normal counterparts.…”
Section: Impact Of Wb Ws and Sm On Meat Qualitymentioning
confidence: 99%
“…The overall appearance of the breasts affected by the myopathies reported in this review is clearly altered as compared to a normal breast muscle (Figure ) and that is a direct consequence of the histological hallmarks of each myopathy: presence of out‐bulging and pale areas of hardened consistency in WB, appearance of white striations of variable thickness parallel to the muscle fibers direction in WS, and the disintegration of the muscle tissue in fiber bundles in SM. Instrumental measurement of the color of WB typically results in elevated lightness ( L * ) (Dalle Zotte et al., ) and increased yellowness ( b * ) (Kuttappan et al., ) with this alterations being worsened at higher degrees of severity (Tasoniero, Cullere, Cecchinato, Puolanne, & Dalle Zotte, ). Discoloration may also be noticeable upon cooking as recently reported by Zhuang and Bowker () who found that the surface of cooked WB fillets was darker, redder, and more yellow than that of fillets without the WB condition.…”
Section: Impact Of Wb Ws and Sm On Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation